2019
DOI: 10.1186/s13075-019-1889-8
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation in systemic sclerosis induces long-lasting changes in B cell homeostasis toward an anti-inflammatory B cell cytokine pattern

Abstract: Background Autologous hematopoietic stem cell transplantation (aHSCT) is performed in patients with aggressive forms of systemic sclerosis (SSc). The profile of B cell reconstitution after aHSCT is not fully understood. The aim of this study was to investigate changes of B cell subsets and cytokine production of B cells in patients with SSc after aHSCT. Methods Peripheral blood of six patients with SSc was collected at defined intervals up to 16 months after aHSCT. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
(50 reference statements)
8
31
0
Order By: Relevance
“…This notion is supported by the previous studies indicating that HSCT results in an active thymogenesis and increased production of naïve T-cells and restoration of immune repertoire after immune recovery approximately 2 years after transplant, resembling the activity level seen in young children 12 34. In a recent study, HSCT also led to a correction of dysfunctional B-cell homoeostasis in SSc by increasing naïve B-cells and decreasing memory, as well as CD27-/IgD double-negative B-cells 35…”
Section: Discussionsupporting
confidence: 63%
“…This notion is supported by the previous studies indicating that HSCT results in an active thymogenesis and increased production of naïve T-cells and restoration of immune repertoire after immune recovery approximately 2 years after transplant, resembling the activity level seen in young children 12 34. In a recent study, HSCT also led to a correction of dysfunctional B-cell homoeostasis in SSc by increasing naïve B-cells and decreasing memory, as well as CD27-/IgD double-negative B-cells 35…”
Section: Discussionsupporting
confidence: 63%
“…The immune reconstitution after aHSCT we present comprises increased B cell numbers, mainly due to increased naïve B cells (accompanied by decreased memory B cells) and decreased CD4 + T cells 1 year after aHSCT. This reconstitution pattern is comparable with previously reported SSc cohorts [ 22 , 23 ], even if different myeloablative protocols (without ATG) were used [ 23 ], and is in concordance with the reconstitution described in patients with systemic lupus erythematodes [ 24 ] and multiple sclerosis [ 25 ]. In contrast, patients with rheumatoid arthritis showed normalized levels of B cells 1 year after aHSCT, although a similar myeloablative protocol was performed [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…In patients with SSc that underwent autologous hematopoietic stem cell transplantation (aHSCT), a peak in the percentage of CD38++/CD10+/IgD+ transitional B cells and CD38++/CD27++/IgD−plasmablasts has been observed already one month after the procedure. These changes persisted for several months after aHSCT and were accompanied by an increased production of IL-10 [45]. As already mentioned for SLE, it has been also observed that SSc patients show altered number and function of IL-10 producing Breg cells [46][47][48].…”
Section: Systemic Sclerosissupporting
confidence: 57%